Usability Issues of Clinical and Research Applications of Virtual Reality in Older People: A Systematic Review - Tuena, Cosimo; Pedroli, Elisa; Trimarchi, Pietro Davide; Gallucci, Alessia; Chiappini, Mattia; Goulene, Karine; Gaggioli, Andrea; Riva, Giuseppe; Lattanzio, Fabrizia; Giunco, Fabrizio; Stramba-Badiale, Marco (Frontiers in Human Neuroscience, 2020)
Aging is a condition that may be characterized by a decline in physical, sensory, mental capacities and increased morbidity, multimorbidity and may be associated with disability. A wide range of clinical conditions (e.g., frailty, mild cognitive impairment, metabolic syndrome) and age-related diseases (e.g., Alzheimer’s and Parkinson’s disease, cancer, sarcopenia, cardiovascular and respiratory diseases) affect older people. Virtual reality (VR) is a novel and promising tool for assessment and rehabilitation in older people. Usability is a crucial factor that must be considered when designing virtual systems for medicine. We conducted a systematic review with Preferred Reporting Items for Systematic reviews and Meta-analysis (PRISMA) guidelines concerning the usability of VR clinical systems in aging and provided suggestions to structure usability piloting. Findings show that different populations of older people have been recruited to mainly assess usability of non-immersive VR, with particular attention to motor/physical rehabilitation. Mixed approach (qualitative and quantitative tools together) is the preferred methodology; technology acceptance models are the most applied theoretical frameworks, however seniors adapted models are the best within this context. Despite minor interaction issues and bug, virtual systems are rated as usable and feasible. We encourage usability and user experience pilot studies to ameliorate interaction and improve acceptance and use of VR clinical applications in older people with the aid of suggestions (VR-USOP) provided by our analysis.